2023
DOI: 10.3390/brainsci13060883
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Approach to the Diagnosis of Autism Spectrum Disorder and Multi-Systemic Developmental Disorder Based on Retrospective Data and ADOS-2 Score

Abstract: Early and accurate diagnosis of autism spectrum disorders (ASD) and tailored therapeutic interventions can improve prognosis. ADOS-2 is a standardized test for ASD diagnosis. However, owing to ASD heterogeneity, the presence of false positives remains a challenge for clinicians. In this study, retrospective data from patients with ASD and multi-systemic developmental disorder (MSDD), a term used to describe children under the age of 3 with impaired communication but with strong emotional attachments, were test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…ML has been effectively applied in the medical field to diagnose neurological disorders, including ASD (Vakadkar et al, 2021 ; Bahathiq et al, 2022 ; Briguglio et al, 2023 ) and ADHD (Slobodin et al, 2020 ; Mikolas et al, 2022 ; Briguglio et al, 2023 ; Kim et al, 2023 ). These studies have demonstrated the potential of ML to increase diagnostic accuracy, reduce time to diagnosis and improve reproducibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ML has been effectively applied in the medical field to diagnose neurological disorders, including ASD (Vakadkar et al, 2021 ; Bahathiq et al, 2022 ; Briguglio et al, 2023 ) and ADHD (Slobodin et al, 2020 ; Mikolas et al, 2022 ; Briguglio et al, 2023 ; Kim et al, 2023 ). These studies have demonstrated the potential of ML to increase diagnostic accuracy, reduce time to diagnosis and improve reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have demonstrated the potential of ML to increase diagnostic accuracy, reduce time to diagnosis and improve reproducibility. For ASD, ML models have been used to identify key traits using sociodemographic, behavioral characteristics, or magnetic resonance imaging (MRI) results, thereby improving and automating the diagnostic process (Vakadkar et al, 2021 ; Bahathiq et al, 2022 ; Briguglio et al, 2023 ). Similarly, ML classifiers for ADHD have been developed based on clinical and psychological data (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…www.ijacsa.thesai.org Interview for Social and Communication Disorder (DISCO) [12]. However, due to the heterogeneity of ASD, the presence of false positive results remains a challenge for clinicians [13]. In addition, clinical examinations are time-consuming and negatively influence the patient behavior because patient is not in the home environment and is surrounded by unfamiliar people and these stimuli may be triggers for crisis-value behaviors.…”
Section: Challenges Of Early Autism Spectrum Disorder Diagnosismentioning
confidence: 99%
“…However, these studies only considered a limited number of features. Machine learning (ML) has been used to consider a wide range of features for identifying ASD cases, including structural differences in brain magnetic resonance imaging (MRI) 1416 , social and behavioural questionnaires 1722 , and gene expression profiles 23,24 . These ML approaches, while promising, are not ethical or feasible when applied across a population.…”
Section: Introduc0onmentioning
confidence: 99%